Dark electrical bias effect on moisture-induced degradation in inverted lead halide perovskite solar cells measured by advanced chemical probes - Sagar Jain (Sustainable Energy & Fuels, 2018)
Emerging lead halide perovskite materials have enormous potential for a range of optoelectronic devices, such as solar cells, light emitting diodes, transistors and lasers. However, the large-scale commercialization of these technologies will depend on the ability of the active material to be stable under environmental and operating conditions. In this work, we measured the first time the electrical bias-induced degradation of inverted perovskite solar cells in the dark in different environments and concluded that humidity coupled with electrical bias results in fast degradation of CH3NH3PbI3 into PbI2. Micro-Raman and photoluminescence show that the degradation starts from the edge of the cell due to moisture ingress. By using novel local Raman-transient photocurrent measurements, we were able to probe local ion migration at the degraded region and non-degraded region and found that the formation of PbI2 can passivate perovskite by reducing ion migration. The degradation is far from uniform across different grains as revealed by secondary electron hyperspectral imaging, an advanced scanning electron microscopy technique which allows probing the composition of individual grain from the cross-section. By using potential step chronoamperometry, we also found that the bias degradation is closely related to the density of mobile ions. The unique combination of established methods with several novel analytical tools provides an insight into the origin of the bias-degradation of inverted perovskite solar cells from nano-scale to cell level, and demonstrates the potential of these novel tools for studying the degradation in other perovskite systems.